Synthesis of Newcastle disease virus polypeptides in a wheat germ cell-free system. - Clinkscales, C W (1977)
We have isolated 18S RNA from cytoplasmic extracts of Newcastle disease virus-infected Chinese hamster ovary cells and tested its ability to direct protein synthesis in extracts derived from wheat germ. The products of the cell-free reaction directed by this RNA contain polypeptides that comigrate with NP, M,F, and 47K roteins from virions. In addition, the products contain a polypeptide (67K) that migrates on polyacrylamide gels slightly faster than the HN protein from virions. Tryptic peptide analysis of the cell-free products and proteins from virions confirms their identity.